Paediatric autoimmune encephalitis: evaluation of clinical features, laboratory investigations and outcome. (24th May 2012) - Hacohen, Y; Wright, S; Clarke, A; Hemingway, C; Wassmer, E; Vincent, A; Lim, M
Abstract : Introduction: Encephalopathy in children and adolescence is associated with a high rate of morbidity and mortality and poses difficult diagnostic and therapeutic challenges. The differential diagnosis is diverse and includes infective, neurometabolic, genetic, neoplastic and inflammatory. It is increasingly recognised that some central nervous system (CNS) disorders can be antibody-mediated. A range of CNS auto antigens have been reported in patients with immune-mediated encephalitis. A growing number of cases have been reported in children, comprising of autoantibodies targeting the voltage-gated potassium channel (VGKC-complex proteins), N-Methyl-D-Aspartic acid (NMDA) and other CNS antigens. Objective: To report the clinical and investigative features of patients with a clinical diagnosis of paediatric autoimmune encephalopathy. Method: 48 patients with encephalopathy (depressed or altered level of consciousness, lasting more than 24 hours, lethargy, or change in personality or behaviour) plus one (or more) of the following; i) seizures, ii) movement disorder, iii) neuropsychiatric symptoms; and iv) cognitive dysfunction, were identified from 110 paediatric patients referred to the Oxford Laboratory for antibody testing. All sera were tested for antibodies to Voltage-gated Potassium Channel (VGKC) and its associated proteins (LGI1 and CASPR2), N-methyl-D-aspartate receptor (NMDAR) and Glycine receptor (GlyR). Results: Seizures (83%), behavioural change (63%) confusion (50%), movement disorder (38%) and hallucinations (25%) were common clinical features. 50% required intensive care support for seizure control or profound encephalopathy. Antibodies were found in 21 patients; NMDAR (13), VGKC (7) and GlyR (1). 56% had infective prodromal symptoms.